PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Pratiwi, Dini (Universitas muhammadiyah palembang, 2017)
The research was conducted to determine the effect of Working Capital Turnover, Receivabl Turnover, and Inventory Turnover to Profitability in Consumer Goods Industry Company in the Indonesia Stock Exchange. The type of data used is the data panel of 10 industry sectors consumer goods companies listed in Indonesia Stock Exchange using the cross section.The results showed that the Working Capital Turnover, Receivable Turnover and Inventory Turnover jointly affect the profitability in the review of the Return On Investment (ROI). indicates that the value of F is equal to 28.0346. is equal to 2.6506. Test conditions, if F count > F table, or F-Statistic prob < ? (0:05), then Ho is rejected. t test results showed that the working capital turnover ((X 1 ) The profitability (Y) can be processed in partially t count variable working capital turnover amounted ttable 1.9721 ? - 6.5253. then there is significant influence by partial working capital turnover on profitability. For receivables turnover variable (X 2 ) to profitability (Y) t count variable receivable turnover amounted -6.64449 while t table 1.9721. it can be concluded that t hitung > t tabel mean a significant difference in partial working capital turnover on profitability. and inventory turnover variable (X 3 ) to profitability (Y) t hitung variable inventory turnover amounted to 4.123983 t table of 1.9721. it can be deduced that there is a significant effect of the partial rotation of working capital on profitability.